2020
DOI: 10.3390/s20195506
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Imprinted Polymer-Based Quartz Crystal Microbalance Sensor for Sensitive Label-Free Detection of Methylene Blue in Groundwater

Abstract: Tiny changes in the mass of the sensor in a quartz crystal microbalance with dissipation monitoring (QCM-D) can be observed. However, the lack of specificity for target species has hindered the use of QCM-D. Here, molecularly imprinted polymers (MIPs) were used to modify a QCM-D sensor to provide specificity. The MIPs were formed in the presence of sodium dodecyl benzene sulfonate. Imprinted layers on Fe3O4 nanoparticles were formed using pyrrole as the functional monomer and cross-linker and methylene blue (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…QCM-based methods were applied for the determination: (i) of low molecular weight analytes [ 240 , 241 ], including histamine [ 242 ], naproxen [ 243 ], ibuprofen [ 244 ], S -propranolol [ 245 ]; (ii) proteins [ 246 , 247 , 248 , 249 ], ribonuclease A [ 250 ], oxidized-low-density lipoprotein in blood serum [ 251 ] and trypsin [ 252 ]; (iii) DNA and [ 249 , 253 ]. More advanced QCM-based techniques such as electrochemical QCM (EQCM) [ 23 , 93 , 254 ] and QCM with dissipation (QCM-D) [ 255 ] were also applied for the determination of analytical signals generated by molecularly imprinted and not imprinted CPs-based sensors.…”
Section: Physicochemical Methods Used For the Determination Of Anamentioning
confidence: 99%
“…QCM-based methods were applied for the determination: (i) of low molecular weight analytes [ 240 , 241 ], including histamine [ 242 ], naproxen [ 243 ], ibuprofen [ 244 ], S -propranolol [ 245 ]; (ii) proteins [ 246 , 247 , 248 , 249 ], ribonuclease A [ 250 ], oxidized-low-density lipoprotein in blood serum [ 251 ] and trypsin [ 252 ]; (iii) DNA and [ 249 , 253 ]. More advanced QCM-based techniques such as electrochemical QCM (EQCM) [ 23 , 93 , 254 ] and QCM with dissipation (QCM-D) [ 255 ] were also applied for the determination of analytical signals generated by molecularly imprinted and not imprinted CPs-based sensors.…”
Section: Physicochemical Methods Used For the Determination Of Anamentioning
confidence: 99%
“…QCM-based determination of the changes of the mass of the formed MIP layer can be simultaneously performed with electrochemical methods and can be used as an electrochemical-QCM (EQCM) method [15,96,237]. A more advantageous QCM-based technique, QCM with dissipation (QCM-D), was also used for the registration of analytical signal generated by MIP-modified resonators [238]. Various optical analytical signal registration methods, including photoluminescence [208,239] surface plasmon resonance (SPR) [240], can also be applied in MIP-based sensors.…”
Section: Physicochemical Methods Used In Molecularly Imprinted Polyme...mentioning
confidence: 99%
“…As a result, the stable and reusable properties have increased the long shelf-life usability of MIPs. Some studies reported the shelf life of MIPs is a minimum of 6 weeks [132] and a maximum of 6 [133] to 12 months [134] for MIP-based biosensors stored at 25 • C. This method is considered a versatile and hopeful technique that can recognize both biological and chemical analytes, including nucleotides [135], amino acids [136], enzymes [137], proteins [138], phosphoproteins [139], viruses [140], bacteria [141], pollutants [142], dyes [143], food poisons [144], pesticides [145], and toxins [146,147].…”
Section: Molecular Imprinting Techniquementioning
confidence: 99%